Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.drugalcdep.2016.08.017
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of delta opioid receptors in alcohol withdrawal-induced mechanical allodynia in male C57BL/6 mice

Abstract: Background As a legal drug, alcohol is commonly abused and it is estimated that 17 million adults in the United States suffer from alcohol use disorder. Heavy alcoholics can experience withdrawal symptoms including anxiety and mechanical allodynia that can facilitate relapse. The molecular mechanisms underlying this phenomenon are not well understood, which stifles development of new therapeutics. Here we investigate whether delta opioid receptors (DORs) play an active role in alcohol withdrawal-induced mechan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 69 publications
1
14
1
2
Order By: Relevance
“…A photo beam-based tracking system was used to track the movement and calculate the time spent in each area. Anxiety-like effects were detected by increasing time spent in the dark compartment ( Alongkronrusmee et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…A photo beam-based tracking system was used to track the movement and calculate the time spent in each area. Anxiety-like effects were detected by increasing time spent in the dark compartment ( Alongkronrusmee et al, 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…Alcohol‐induced hyperalgesia can also be observed in mouse models (Alongkronrusmee et al, ; Bergeson et al, ; Smith et al, ), which allows for powerful genetic manipulations. For example, Alongkronrusmee and colleagues () recently reported that male wild‐type (WT) and δ‐opioid receptor (DOR) knockout C57BL/6 mice that were allowed to self‐administer alcohol (10%) versus water for 3 weeks in a 2‐bottle choice drinking‐in‐the‐dark (4 h/d) procedure exhibited escalation of alcohol intake to ~ 4 g/kg in 4 hours. A few days into alcohol abstinence, both groups exhibited mechanical hypersensitivity in the von Frey test, but this effect was exacerbated in DOR knockout mice.…”
Section: Preclinical Models To Investigate the Intersection Of Aud Anmentioning
confidence: 99%
“…Furthermore, deficits in brain-derived neurotrophic factor expression and dendritic spine density in amygdaloid circuits in response to chronic alcohol and withdrawal are also attenuated by trichostatin A (Pandey et al, 2008; You et al, 2014), which is mechanistically consistent with the role of this brain region in regulation of negative affect (Pandey et al, 2017). Pain represents another behavioral phenotype of negative affect, which develops during withdrawal (Edwards et al, 2012; Alongkronrusmee et al, 2016; Smith et al, 2016; Avegno et al, 2018; Kononoff et al, 2018) and can play a critical role in maintaining addictive behaviors (Egli et al, 2012; Apkarian et al, 2013). To the best of our knowledge, the effects of HDAC inhibitor treatment on ethanol withdrawal-induced hyperalgesia has not been investigated.…”
Section: Introductionmentioning
confidence: 99%